CONSTRUCTION OF THE STRENGTH STATISTICAL CRITERIA WITH CONSIDERATION OF SOME BRITTLE MATERIALS FAILURE DETERMINISTIC ASPECTS FEATURES - Kvit, R. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
The model of a stochastically defective plate from an isotropic material under conditions of comprehensive tension-compression is considered. Defect-cracks are characterized by two statistically independent geometric parameters, whose laws of probabilistic distribution are given. Based on the deterministic failure criteria, which takes into account the initial direction of the crack propagation, the statistical diagrams equations of the plate strength are written in the fracture loading mean values. Such diagrams are constructed for plates with different defect structure and different structure materials inhomogeneity. The effect of taking into account the initial direction of the crack propagation on the obtained limiting state curves is investigated.